Pulsed Power Plasma Stimulation: A Comprehensive Review and Field Insights - Son T. Nguyen; Mohamed E.-S. El-Tayeb; Mohamed Adel Gabry; Mohamed Y. Soliman (Energies)
Pulsed Power Plasma Stimulation (3PS) represents a promising and environmentally favorable alternative to conventional well stimulation techniques for enhancing subsurface permeability. This comprehensive review tracks the evolution of plasma-based rock stimulation, offering insights from key laboratory, numerical, and field-scale studies. The review begins with foundational electrohydraulic discharge concepts and progresses through the evolution of Pulsed Arc Electrohydraulic Discharge (PAED) and the more advanced 3PS systems. High-voltage, ultrafast plasma discharges generate mechanical shockwaves and localized thermal effects that result in complex fracture networks, particularly in tight and crystalline formations. Compared to conventional well stimulation techniques, 3PS reduces water use, avoids chemical additives, and minimizes induced seismicity. Laboratory studies demonstrate significant improvements in permeability, porosity, and fracture intensity, while field trials show an increase in production from oil, gas, and geothermal wells. However, 3PS faces some limitations such as short stimulation radii and logistical constraints in wireline-based delivery systems. Emerging technologies like plasma-assisted drilling and hybrid PDC–plasma tools offer promising integration pathways. Overall, 3PS provides a practical, scalable, low-impact stimulation approach with broad applicability across energy sectors, especially in environmentally sensitive or water-scarce regions.